The role of AGN feedback in the structure, kinematics, and evolution of ETGs in Horizon simulations - Rosito, MS; Pedrosa, SE; Tissera, PB; Chisari, NE; Domínguez-Tenreiro, R; Dubois, Y; Peirani, S; Devriendt, J; Pichon, C; Slyz, A (EDP Sciences, 2021)
Context. Feedback processes play a fundamental role in the regulation of the star formation (SF) activity in galaxies and, in particular, in the quenching of early-type galaxies (ETGs) as has been inferred by observational and numerical studies of Λ-CDM models. At z = 0, ETGs exhibit well-known fundamental scaling relations, but the connection between scaling relations and the physical processes shaping ETG evolution remains unknown.